Complex Living Conditions Impair Behavioral Inhibition but Improve Attention in Rats - van der Veen, Rixt; Kentrop, Jiska; van der Tas, Liza; Loi, Manila; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Joëls, Marian (Frontiers in Behavioral Neuroscience, 2015)
Rapid adaptation to changes, while maintaining a certain level of behavioral inhibition is an important feature in every day functioning. How environmental context and challenges in life can impact on the development of this quality is still unknown. In the present study, we examined the effect of a complex rearing environment during adolescence on attention and behavioral inhibition in adult male rats. We also tested whether these effects were affected by an adverse early life challenge, maternal deprivation. We found that animals that were raised in large, two floor MarlauTM cages, together with 10 conspecifics, showed improved attention, but impaired behavioral inhibition in the 5-choice serial reaction time task. The early life challenge of 24h maternal deprivation on postnatal day 3 led to a decline in bodyweight during adolescence, but did not by itself influence responses in the 5-choice task in adulthood, nor did it moderate the effects of complex housing. Our data suggest that a complex rearing environment leads to a faster adaptation to changes in the environment, but at the cost of lower behavioral inhibition.